Progress in Materials Science and Engineering - Brebbia, Carlos; Connor, Jerome J. (Innovation and Discovery in Russian Science and Engineering, 2018)
This book presents recent advances made in materials science and engineering within Russian academia, particularly groups working in the Ural Federal University District. Topics explored in this volume include structure formation analysis of complicated alloys, non-ferrous metals metallurgy, composite composed materials science, and high-pressure treatment of metals and alloys. The finding discussed in this volume are to critical to multiple industries including manufacturing, structural materials, oil and gas, coatings, and metal fabrication. Maximizes reader understanding of materials research in Russia relevant to multiple industries including manufacturing, structural materials, oil and gas, coatings, and metal fabrication; Sheds light on R&D strategies developed within the foremost Russian universities; Details specific cases of issues, problems, and solutions within the Russian materials manufacturing and formulation sectors.